Botānikas katedras mācību preparāti - Jamonte, Daiga (My University, 2020)
Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās glabājas vēl Rīgas Politehniskā institūta (1896—1918) mācību preparāti, kas vēlākos gados ir izmantoti LU Botānikas katedrā. Raksts iepazīstina ar mikrosēņu mācību preparātiem un mikologa Jūlija Smaroda (1884 – 1956) “Latvijas sēņu eksikāts” (Fungi latvici exiccati) kolekcijām.

The collections of Botany and Mycology of the Museum of the University of Latvia also contain teaching preparations of the Riga Polytechnic Institute (1896–1918), which were used in later years at the Department of Botany of the University of Latvia. The article introduces microfungi teaching preparations and the collections of mycologist Julij Smarod’s (1884 – 1956) “Latvian mushroom exsiccati” (Fungi latvici exiccati).
Teaching preparations of the Department of Botany
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; mikrosēnes; mycology; LU Botānikas katedra; Jūlijs Smarods; izglītība; mācību līdzekļi; zinātnes vēsture; Vēsture - Latvijas Universitāte; Vēsture - Rīgas Politehniskais institūts